A novel split mode TFBAR device for quantitative measurements of prostate specific antigen in a small sample of whole blood. Issue 17 (22nd April 2020) - Wajs, Ewelina; Rughoobur, Girish; Burling, Keith; George, Anne; Flewitt, Andrew J.; Gnanapragasam, Vincent J.
Abstract : TFBAR technology demonstrates a cost-effective means for point-of-care diagnostics and monitoring of PSA. Abstract : Easy monitoring of prostate specific antigen (PSA) directly from blood samples would present a significant improvement as compared to conventional diagnostic methods. In this work, a split mode thin film bulk acoustic resonator (TFBAR) device was employed for the first time for label-free measurements of PSA concentrations in the whole blood and without sample pre-treatment. The surface of the sensor was covalently modified with anti-PSA antibodies and demonstrated a very high sensitivity of 101 kHz mL ng −1 and low limit of detection (LOD) of 0.34 ng mL −1 in model spiked solutions. It has previously been widely believed that significant pre-processing of blood samples would be required for TFBAR biosensors. Importantly, this work demonstrates that this is not the case, and TFBAR technology provides a cost-effective means for point-of-care (POC) diagnostics and monitoring of PSA in hospitals and in doctors' offices. Additionally, the accuracy of the developed biosensor, with respect to a commercial auto analyser (Beckman Coulter Access), was evaluated to analyse clinical samples, giving well-matched results between the two methods, thus showing a practical application in quantitative monitoring of PSA levels in the whole blood with very good signal recovery.